Institutional Liquidity Needs and the Structure of Monitored Finance: Table 1 - Winton, Andrew (Review of Financial Studies, 2003)
A financial institution that finances and monitors firms learns private information about these firms. When the institution seeks funds to meet its own liquidity needs, it faces adverse selection ("liquidity") costs that increase with the risk of its claims on these firms. The institution can reduce its liquidity costs by holding debt rather than equity. Conversely, except in a limited setting resembling venture capital, firms that depend on monitored finance prefer to give the monitoring institution debt rather than equity. Institutions with less frequent or less severe liquidity needs have greater appetite for equity and for the debt of more risky borrowers. These predictions are consistent with general patterns of monitored finance. Copyright 2003, Oxford University Press.